2020
DOI: 10.1038/s41598-020-58389-6
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic prospects of a seaweed bioeconomy in Sweden

Abstract: Seaweed cultivation is a large industry worldwide, but production in Europe is small compared to production in Asian countries. In the EU, the motivations for seaweed farming may be seen from two perspectives; one being economic growth through biomass production and the other being the provisioning of ecosystem services such as mitigating eutrophication. In this paper, we assess the economic potential of large-scale cultivation of kelp, Saccharina latissima, along the Swedish west coast, including the value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…The latter include investments, payment of energy costs (for instance, in order to ensure adequate agitation) and deployment of abundant water resources, which are expensive in many countries. However, some case-studies limited to particular countries have concluded that macroalgal cultivation may be profitable (Hasselström et al, 2020).…”
Section: Macroalg Ae Produc Tionmentioning
confidence: 99%
“…The latter include investments, payment of energy costs (for instance, in order to ensure adequate agitation) and deployment of abundant water resources, which are expensive in many countries. However, some case-studies limited to particular countries have concluded that macroalgal cultivation may be profitable (Hasselström et al, 2020).…”
Section: Macroalg Ae Produc Tionmentioning
confidence: 99%
“…Coastal and marine stakeholders were also subject to adverse impacts in two of these social-impact pathways. SA installations led to increased claims on available space which was hypothesised to create spatial competition and interference across environmental protection objectives, fishery operations and leisure uses ( Hasselström et al, 2020 ;Gjertsen et al, 2020 ;Miah et al, 2020 ;Gegg and Wells, 2019 ;Hasselström et al, 2018 ).…”
Section: Potential Consequences To Society Including Economic and Non...mentioning
confidence: 99%
“…By allowing to identify impacting hotspots within the aquaculture value chain, improvements can be implemented towards increased sustainability. For instance, LCA studies applied to large‐scale cultivation of the brown algae Saccharina latissima , suggested that seaweed farming has the potential of becoming a profitable industry in North West Europe, 230,231 with great promise to reduce the resource footprint of seaweed cultivation once energetic efficiency is improved (electricity and transport) and biomass productivity increases; 230,232 and/or improvements on infrastructural component materials (eg stainless steel chains, polypropylene ropes) and system design (eg number of cultivation strips in the water column) are employed 233 . Similarly, an explorative LCA study performed to evaluate the environmental impacts of producing bioplastics from green macroalgae ( Ulva spp.)…”
Section: Future Perspectivesmentioning
confidence: 99%